Design of mechanically compensated Penning trap for the study of ions in extreme laser field. (August 2015) - Kumar, Sugam; Vogel, M; Quint, W; Ringleb, S; Stöhlker, Th; Safvan, C P
Synopsis: This paper describes the design of a mechanically compensated Penning trap as a versatile tool to confine atomic ions in static electric and magnetic fields for the study of non-linear processes such as multi-photon ionization from well-defined initial charge states interacting with a large range of photon energies by nondestructive observation.